Global Social Movements (GSMs) and Non-Governmental Organizations: Investigating the Impact on Global Social Change - Nandy, Debasish (Department of Public Administration, 2024)
Global Social Movements (GSMs) have become integral to the study of Sociology and International Politics, reflecting the interconnectedness of global communities on diverse issues. Orchestrated by NGOs and INGOs, GSMs encompass environmental, women’s, human rights, racial, fair trade, and refugee movements, among others, reflecting the breadth of global concerns. However, challenges arise from political affiliations between civil society members and state authorities, as well as pressures from donor countries and ruling elites in economically disadvantaged nations. This study, employing content analysis methodology, aims to delineate the causes of GSMs, investigate the roles of INGOs and civil society, and explore the interplay between GSMs and global governance. Through critical analysis, it provides insights and recommendations to enhance the effectiveness and inclusivity of GSMs in addressing global challenges, thus contributing to the advancement of global democracy and governance structures.